Association between body mass index and regulation of the cardiovascular system in medical students. A pilot study - Alvarado-Aravena, Caren; Castillo-Aguilar, Matias; Retamal-Matus, Hector Felipe; Estrada Goic, Claudia Andrea; Nuñez Espinosa, Cristian Andrés (My University, 2021)
Objective: this study had the purpose of knowing the association of the body mass index and cardiovascular regulation of medical students. Materials and methods: a cross-sectional study with a randomized design. The sample consisted of 54 medical students (21,2 +/- 1,6 years) who were evaluated and classified according to the body mass index: Normal weight (NP; BMI <25 kg / m(2)); Overweight (SP; BMI >= 25 kg / m(2)); Obese (OB; BMI >= 30 Kg / m(2)). Anthropometric measurements, blood pressure, and heart rate variability (HRV) were the variables evaluated. Results: 51,9% of the students are overweight or obese. The body mass index was negatively correlated with the heart rate variability parameter, especially when compared with the HRV time domains (p <0.001). Differences were also observed in cardiac autonomic control when comparing the study groups in LnRMSSD (p <0,01) and LnSDNN (p <0,01). Conclusion: the implementation of measures that decrease BMI values will allow greater autonomic cardiac control and better cardiovascular health in medical students.
Keywords: body composition; heart rate; blood pressure; medical students